INTEGRASI PEMBELAJARAN FIKIH WANITA DALAM MENJAGA KESEHATAN REPRODUKSI REMAJA PADA SANTRIWATI AL-ISLAM YOGYAKARTA - Fitri, Zulfa Laila; Waharjani; Jannatul Husna (Jurnal Studi Pesantren, 2025)
Reproductive health education for adolescents is a crucial issue due to the high number of cases of unwanted pregnancies and sexual violence involving teenagers. This study aims to explore how the teaching of Fiqh Wanita (Islamic jurisprudence for women) helps maintain adolescent reproductive health among female students at Al-Islam Islamic boarding school in Yogyakarta. The research employs a qualitative approach with a case study method, utilizing observation, interviews, and documentation for data collection. The findings reveal that the Fiqh Wanita curriculum at Al-Islam integrates reproductive health topics by combining religious teachings with health knowledge. Lectures, discussions, and evaluations are the primary teaching methods employed. The female students demonstrate a strong understanding of the importance of maintaining reproductive health, aligning with Islamic teachings that encompass both physical and moral aspects.